Analysis of Platelet Volume Indices in Patients with Acute Coronary Syndrome in Gujarat, India - Shubhi Saxena; Nishant Saxena; Richa Jain; Jasmin Jasani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Coronary artery disease (CAD) is growing in heaps and bounces with increasing incidencesevery year due to increase in cardiovascular risk factors like diabetes mellitus, obesity, smoking, hypertension,dyslipidemia and sedentary life style. Platelets have always been a cornerstone of thrombosis, aggravationof atherosclerosis and its complications, such as acute coronary syndromes which include acute myocardialinfarction (AMI), Non ST Elevation MI (NSTEMI) and unstable angina (UA), and sudden cardiac death.Platelet aggregation and activation plays a pivotal role in thrombus generation in cardiovascular diseases.The aim of this study is to evaluate platelet indices in coronary artery disease and to reveal a clinicaldiscussion based on them.Methods: A total of 65 cases were studied; 21 patients had stable coronary artery disease for which theywere admitted for a coronary angiogram. 27 patients had Troponin negative unstable angina (UA) or troponinpositive NSTEMI or STEMI having corresponding ECG findings. The third group had a normal cardiogram.Conclusion: Platelet Volume Indices studied were — mean platelet volume (MPV), platelet large cellratio (PLCR), platelet distribution width (PDW) was increased in ACS as compared to stable CAD and thecontrol group. Large platelets are functionally notorious and are a predisposing contributor for developingmyocardial infarction. Larger platelets can be diagnosed routinely by CBC’s, Platelet volume indices arecommon, cheap and easily available tool for screening future thrombotic cardiovascular diseases.